2015
DOI: 10.1158/1535-7163.mct-15-0129
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Circadian Determinants of Cancer Chronotherapy through In Vitro Chronopharmacology and Mathematical Modeling

Abstract: Cancer chronotherapy aims at enhancing tolerability and efficacy of anticancer drugs through their delivery according to circadian clocks. However, mouse and patient data show that lifestyle, sex, genetics, drugs, and cancer can modify both host circadian clocks and metabolism pathways dynamics, and thus the optimal timing of drug administration. The mathematical modeling of chronopharmacology could indeed help moderate optimal timing according to patient-specific determinants. Here, we combine in vitro and in… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
73
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 61 publications
(77 citation statements)
references
References 31 publications
4
73
0
Order By: Relevance
“…TOP1 is also the target enzyme of the anticancer drug irinotecan, whose inhibition results in DNA breaks and cellular apoptosis. TOP1 mRNA and cytoplasmic protein levels displayed circadian rhythms in synchronized cell cultures of a human colorectal cancer model at confluence (Dulong et al, 2015). Although it has been shown that the protein dimer CLOCK-BMAL1 promotes TOP1 transcription, the circadian regulation of TOP1 expression remains still mostly unknown.…”
Section: Systems Approaches Toward Personalized Chronotherapeuticsmentioning
confidence: 99%
See 4 more Smart Citations
“…TOP1 is also the target enzyme of the anticancer drug irinotecan, whose inhibition results in DNA breaks and cellular apoptosis. TOP1 mRNA and cytoplasmic protein levels displayed circadian rhythms in synchronized cell cultures of a human colorectal cancer model at confluence (Dulong et al, 2015). Although it has been shown that the protein dimer CLOCK-BMAL1 promotes TOP1 transcription, the circadian regulation of TOP1 expression remains still mostly unknown.…”
Section: Systems Approaches Toward Personalized Chronotherapeuticsmentioning
confidence: 99%
“…The chronoefficacy rhythms may at least partly originate from the circadian control of drug metabolism and distribution at the whole-body level, which influences tumor drug concentrations. In contrast, in vitro studies have shown that some cancer cell lines, such as human breast cancer MCF-7, have lost circadian rhythmicity in clock gene transcription (Xiang et al, 2012), whereas others such as human colon cancer Caco-2 at confluence have retained coordinated circadian expression (Dulong et al, 2015). However, most studies in vivo have shown the lack of consistent 24-hour patterns in experimental cancer tissues, especially for poorly differentiated carcinomas (Lévi et al, 2010).…”
Section: Cancer As a Driver For Systems Chronotherapeuticsmentioning
confidence: 99%
See 3 more Smart Citations